Progressive systemic sclerosis of the internal anal sphincter leading to passive faecal incontinence. - Engel, A F (1994)
Two female patients aged 62 and 44 years with progressive systemic sclerosis and passive faecal incontinence are described. Both had the typical gut motility disorders of dysphagia, heartburn, and constipation. Anorectal physiology tests showed a low resting pressure in both and an absent rectoanal inhibitory reflex in one. In both patients anal endosonography showed a thin internal anal sphincter with changed reflectivity suggestive of fibrosis. In both patients anorectal sensation and pudendal nerve function were normal. Histological examination of the rectum in one patient showed collagenous replacement of the rectal muscularis propria with prominent atrophy of the musculature. This study suggests that the internal sphincter may be selectively affected by progressive systemic sclerosis, which may lead to passive faecal incontinence.